Handbook of biomolecules fundamentals, properties and applications - Verma, Chandrabhan; Verma, Dakeshwar Kumar (Elsevier, 2023)
"Handbook of Biomolecules: Fundamentals, Properties and Applications is a comprehensive resource covering new developments in biomolecules and biomaterials and their industrial applications in the fields of bioengineering, biomedical engineering, biotechnology, biochemistry, and their detection methods using biosensors. This book covers the fundamentals of biomolecules, their roll in living organism, structure, sources, important characteristics, and the industrial applications of these biomaterials. Sections explore amino acids, carbohydrates, nucleic acids, proteins, lipids, metabolites and natural products, then go on to discuss purification techniques and detection methods. Applications in biomolecular engineering, biochemistry and biomedical engineering, among others, are discussed before concluding with coverage of biomolecules as anticorrosion materials."